2014
DOI: 10.4067/s0717-95022014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Músculo Aductor Mínimo en Individuos Brasileños

Abstract: RESUMEN:Entre el grupo muscular que realiza la aducción de la articulación del cuadril se destaca el músculo aductor magno, cuya porción superior de la parte aductora puede constituir el músculo aductor mínimo. En la literatura hay pocas citaciones sobre este músculo, más allá de la presencia de datos divergentes entre diversos autores. De este modo, el objetivo de este estudio ha sido el de analizar el músculo aductor mínimo con relación: a sus inserciones proximal y distal, a las disposiciones de las fibras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The AMi is small, flat, and can be distinguished at the posterior part of the adductor brevis and the upper part of the AMa [22]. This muscle originates predominantly from the inferior ramus of the pubis [22] or the ischiopubic ramus [23] and inserts into the femur, and is innervated by the obturator nerve. The descriptions of the origin and insertion of the muscle are broadly consistent in the anatomical literature, whereas those related to distinguishing the muscle have been inconsistent: some authors have regarded this muscle as the upper part of the AMa [24][25][26][27], while others have suggested that it is independent of adjacent muscles [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMi is small, flat, and can be distinguished at the posterior part of the adductor brevis and the upper part of the AMa [22]. This muscle originates predominantly from the inferior ramus of the pubis [22] or the ischiopubic ramus [23] and inserts into the femur, and is innervated by the obturator nerve. The descriptions of the origin and insertion of the muscle are broadly consistent in the anatomical literature, whereas those related to distinguishing the muscle have been inconsistent: some authors have regarded this muscle as the upper part of the AMa [24][25][26][27], while others have suggested that it is independent of adjacent muscles [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Some textbooks do not even mention this muscle at all [30(31)-32 (33)]. The AMi is normally present in apes such as gorillas and chimpanzees [34], while its incidence in humans has been reported as 32% to 92% of the specimens according to the different populations [22,23,35] ( Table 3). The present study found that its incidence was 94.4% in Korean cadavers, which was similar with the previous study using same race [35].…”
Section: Discussionmentioning
confidence: 99%